Master of Science (MSc) Program in Radiation Biology: An Interdepartmental Course Bridging the Gap between Radiation-Related Preclinical and Clinical Disciplines to Prepare Next-Generation Medical Scientists - Combs, Stephanie E.; Kessel, Carmen; Wilkens, Jan J.; Multhoff, Gabriele; Schmid, Thomas E.; Vaupel, Peter; Trott, Klaus-Rüdiger; Berberat, Pascal; Atkinson, Michael J. (Frontiers in Oncology, 2017)
Radiation biology is a highly interdisciplinary field at the interface of biology, physics and medicine. It is characterized by rapid advances in biological and technical knowledge. The potential for using these advances to optimize medical care, radiation protection and related fields can only be exploited with complementary activities to support the education of young academics. A small number of academic institutions have committed resources into radiation-related courses and curricula; however, few offer a comprehensive interdepartmental research and training program. At the Technical University Munich (TUM), a full MSc course in radiation biology has been established. This paper describes the TUM MSc radiation biology program, discusses the scope of the field, the teaching goals as well as the interdisciplinary curriculum. Detailed information on the full MSc program can be found continuously updated at www.radonc.med.tum.de/masterradiationbiology.